Apoptotic effects of Corchorus olitorius L. leaf extracts in colon adenocarcinoma cell lines - Soykut, Gunsu; Becer, Eda; Calis, Ihsan; Yucecan, Sevinc; Vatansever, Seda (Progress in Nutrition, 2018)
Corchorus olitorius L. is a highly consumed plant in Cyprus and other Eastern Mediterranean countries and known as a medicinal food in many cultures.  The aim of the study is to determine in vitro anticancer and apoptotic induction effects of dichloromethane (DCM) and aqueous Corchorus olitorius L.  leaf extracts in primary (Colo-320) and metastatic (Colo-741) colon adenocarcinoma cell lines.. Cell growth and cytotoxicity were measured with MTT assay with five different concentrations of extracts in Colo-320 and Colo-741 cell lines. Apoptotic activities of Corchorus olitorius L. were investigated by immunocytochemistry using antibodies directed against to caspase-3, cytochrome-c and FasLigand (FasL). TUNEL assay was used to detect DNA fragmentation in both cell lines. Both DCM and aqueous phase of extracts at 50 µg/ml concentration were more effective at inhibiting Colo-320 and Colo-741 cell growth when compared with other dilutions. The number of TUNEL positive cells was significantly higher in Colo-741  cells when compared with both control group and Colo-320 cell line. DCM phase extract significantly increased caspase-3 immunoreactivity while aqueous phase extract significantly increased cytochrome-c and FasLigand (FasL) immunoreactivities in Colo-320 cell lines. Both extracts were able to significantly increase caspase-3, cytochrome-c and FasL immunoreactivity in Colo-741 cells showing that both apoptotic pathways were triggered. Overall, Corchorus olitorius L. extracts induced apoptosis in both cancer cell lines while being more effective in metastatic colon adenocarcinoma cell lines suggesting that the extracts might have potential anticancer effects and possibility to be used as precursor to phytomedicinal colon cancer treatment as oppose to chemotherapy.